Prospective Randomized Comparison of Oral Sodium Phosphate and Sennoside A plus B Calcium Lavage for Colonoscopy Preparation - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2011)
Purpose: The aim of this study is to assess 2 different bowel-cleansing agents. Methods: The patients were prospectively randomized to 2 arms of sodium phosphate versus Sennoside A+B calcium preparation. Laboratory assessment, body weight, height, and vital signs were obtained at baseline and before colonoscopy. A self-administered questionnaire was completed by the patients. The time taken to complete the colonoscopy and the segment of the colon examined were recorded. Results: The patients in the Sennoside A+B calcium group were more comfortable with the taste of the solution. Patients using sodium phosphate faced more nausea and significantly lower Ca levels and P values. The pulse rate was significantly higher in this group. Patients in the sennoside group had better grades of bowel cleansing in sigmoid and descending segments of the colon. Conclusions: Sennoside A+B calcium is more effective in some of the colonic segmental cleansing, causes fewer changes on serum electrolyte levels, and is better tolerated.
Keywords: colonoscopy preparation; sennoside; sodium phosphate; BOWEL PREPARATION; EFFICACY; SEIZURES; PATIENT; TRIAL; COLON